Supporting children: Victims of crime, within victim support - Walle Vande Ilse (Temida, 2004)
All too often, the victimization of children is automatically associated with child abuse and sexual abuse. However, children are also confronted, either directly or indirectly, with other kinds of criminality. In spite of that children usually do not get appropriate support and assistance. In this paper, the establishment and development of services for the support of children-victims of crime in Belgium, as well as European cooperation in this regard, are described.